2013
DOI: 10.1186/1866-1955-5-7
|View full text |Cite
|
Sign up to set email alerts
|

Social and emotional processing in Prader-Willi syndrome: genetic subtype differences

Abstract: BackgroundPeople with Prader-Willi syndrome (PWS) demonstrate social dysfunction and increased risk of autism spectrum disorder, especially those with the maternal uniparental disomy (mUPD) versus paternal deletion genetic subtype. This study compared the neural processing of social (faces) and nonsocial stimuli, varying in emotional valence, across genetic subtypes in 24 adolescents and adults with PWS.MethodsUpright and inverted faces, and nonsocial objects with positive and negative emotional valence were p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 65 publications
1
20
3
Order By: Relevance
“…The initial screen by JB and TG resulted in 27 full‐text articles to be reviewed for eligibility. For the entire systematic review, seven articles were excluded either because of a lack of focus on core ASD symptoms or failure to report prevalence of ASD in those with PWS [Cotton and Richdale, ; Halit et al, ; Dimitropoulos et al, ; Cotton and Richdale, ; Key et al, ; Bruining et al, ; Feldman and Dimitropoulos, ]. For the study aim of investigating ASD core domains in PWS, an additional five articles were not included in the analysis [Beardsmore et al, ; Hou et al, ; Akefeldt and Gillberg, ; Descheemaeker et al, ; Reilly et al, ].…”
Section: Resultsmentioning
confidence: 99%
“…The initial screen by JB and TG resulted in 27 full‐text articles to be reviewed for eligibility. For the entire systematic review, seven articles were excluded either because of a lack of focus on core ASD symptoms or failure to report prevalence of ASD in those with PWS [Cotton and Richdale, ; Halit et al, ; Dimitropoulos et al, ; Cotton and Richdale, ; Key et al, ; Bruining et al, ; Feldman and Dimitropoulos, ]. For the study aim of investigating ASD core domains in PWS, an additional five articles were not included in the analysis [Beardsmore et al, ; Hou et al, ; Akefeldt and Gillberg, ; Descheemaeker et al, ; Reilly et al, ].…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, both neural and genetic studies suggest similarities between PWS, ASD, schizophrenia, and psychosis [ 45 ]. Examining evoked response potential’s (ERP) to images of faces, Key and colleagues [ 46 ] found that individuals with PWS due to mUPD, but not deletions, showed a lack of visual ERP face-specific amplitude increase in N170, a robust pattern also seen in autism and schizophrenia [ 47 ]. Based on structural magnetic resonance imaging, Lukoshe et al [ 48 ] concluded that children with PWS due to mUPD have early deviations in brain development that are reminiscent of those in ASD or schizophrenia.…”
Section: Discussionmentioning
confidence: 99%
“…Some of these features vary across genetic subtypes of PWS. Those with Type I deletions, for example, generally show lower cognitive or adaptive behavior skills, while those with mUPD may have better‐developed verbal than spatial skills, and are more apt to have autism, autistic features and psychosis (Boer et al., ; Dykens, Lee, & Roof, ; Dykens & Roof, ; Key, Jones, & Dykens, ; Whittington et al., ).…”
Section: Introductionmentioning
confidence: 99%